2019
DOI: 10.1371/journal.pone.0218214
|View full text |Cite
|
Sign up to set email alerts
|

Resource planning of Chinese commercial banking systems using two-stage inverse data envelopment analysis with undesirable outputs

Abstract: This paper develops two-stage inverse data envelopment analysis models with undesirable outputs to formulate resource plans for 16 Chinese listed commercial banks whose outputs are increased and overall efficiency is kept unchanged in the short term. We use these models to meet three different output targets, namely, increasing both the desirable and undesirable outputs by the same percentage, increasing these outputs by different percentages, and increasing only the desirable outputs while keeping the undesir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Within the non-parametric approach, DEA, which is an efficiency frontier technique, is broadly used to measure banking performance (Alam et al, 2021). For instance, DEA was applied to examine the efficiency of British commercial banks (Ouenniche & Carrales, 2018), banks in the USA (Kwon and Lee, 2015), and worldwide banking efficiency (Ahmad & Prentice, 2019;An et al, 2019;Banya & Biekpe, 2018;Chowdhury & Haron, 2021;Henriques et al, 2018;Kamarudin et al, 2019;Tamatam et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Within the non-parametric approach, DEA, which is an efficiency frontier technique, is broadly used to measure banking performance (Alam et al, 2021). For instance, DEA was applied to examine the efficiency of British commercial banks (Ouenniche & Carrales, 2018), banks in the USA (Kwon and Lee, 2015), and worldwide banking efficiency (Ahmad & Prentice, 2019;An et al, 2019;Banya & Biekpe, 2018;Chowdhury & Haron, 2021;Henriques et al, 2018;Kamarudin et al, 2019;Tamatam et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In contrast, UCBs should improve their technical and management level and strive to narrow the gap with joint-stock banks. According to the two-stage inverse DEA with undesirable outputs, An et al (2019) suggested that China's commercial banks should do the following: (1) increase their operating costs and interest expenses to fulfill their short-term tasks; (2) keep the amount of deposits at a reasonable and effective level; (3) improve the business level of their employees; and (4) scrutinize the creditworthiness of their borrowers. Large-scale group decision-making (LSGDM) problems in the banking industry also need to be improved.…”
Section: Management Of Commercial Banksmentioning
confidence: 99%
“…While this study confirms this view, it also finds that UCBs have recently been performing better despite lagging behind in earlier years. In addition, existing studies (see, e.g., An et al 2019;Chen et al 2020) suggested that banks need to strengthen their management of non-performing loans. This paper also finds that commercial banks need to pay attention to the investment stage.…”
Section: Conclusion and Suggestionsmentioning
confidence: 99%
“…Ghiyasi and Khoshfetrat (2019) introduced an alternative inverse DEA model to determine interval inputs for altering interval outputs as long as the interval efficiencies of all entities remain without change. An et al (2019) developed a two-stage inverse DEA approach with undesirable outputs for concerning resources while all measures were precise. Kalantary et al (2018) evaluated the sustainability of chains with precise measures using their inverse dynamic network range-adjusted measure strategy.…”
Section: Introductionmentioning
confidence: 99%